In vitro microleakage of a fissure sealant polymerized by either a quartz tungsten halogen curing light or a plasma arc curing light - SARAH SHAH, ELIZABETH M. ROEBUCK, ZOANN NUGENT, & CHRIS DEERY (IAPD and Blackwell, 2007)
A pit and fissure sealant (sealant) is a material that obliterates or seals any pits and fissures when applied to the surface of a tooth. A large number of studies have demonstrated that sealants are effective in caries prevention.